Pilgrim's guide to Guruvayoor & a few other temples, 1982 - Nayar, S. P. (S. Prabhakaran), 1925- (Progressive Printers & Publishers, 1982)
On the Guruvayurappan Temple, Guruvayur, and other Hindu pilgrimage centers in Kerala and Karnataka.